An Analysis of Learning Style Preferences and Student Participation in General English Courses at the Management Study Program, Universitas Muhammadiyah Bengkulu” - mike siltia; Ivan Achmad Nurcholis; Kiagus Baluqia; Ririn Putri Ananda (Teaching English and Language Learning English Journal, 2026)
This research aimed to analyze students’ learning style preferences and to describe the level of student participation in the General English course of the English Education Program at Universitas Muhammadiyah Bengkulu. This research also aimed to identify how students’ learning styles were reflected in their classroom participation.This research used a descriptive quantitative method. The population of this research was the first semester 2025/2026 student of the management study program at Universitas Muhammadiyah Bengkulu. The sample consisted of 50 students who were selected using total sampling. The data were collected through a questionnaire based on the VARK learning style model and student participation indicators. In addition, interviews were conducted to support and strengthen the data obtained from the questionnaire. The data from the questionnaire were analyzed using mean scores, while the interview data were analyzed descriptively.The results showed that students had diverse learning style preferences. The auditory learning style was the most dominant (mean = 3.94), followed by read/write (3.83), kinesthetic (3.77), and visual (3.69). In terms of participation, the results indicated that students’ classroom participation was generally at a high level. Students showed the highest participation in practicing English (mean = 4.42) and completing tasks (mean = 4.36), while answering questions had the lowest mean score (3.30) which was categorized as moderate. The interview results supported the questionnaire findings by showing that students with dominant auditory learning styles tended to participate actively in listening, discussions, and classroom activities.In conclusion, the findings indicate that students have different learning style preferences, with auditory learning style being the most dominant, and that students generally demonstrate a high level of participation in the classroom.